Study on the classification and identification of Blog pages - ZHENG De-quan; ZHANG Di; ZHAO Tie-jun; YU Hao (Tongxin xuebao)
In order to find an automatic way to recognize the Blog pages from other Web pages for the content extraction of the Blog pages and other researches.According to the characteristic of Blog pages,some basic concepts and ideas in the area of Blog was described,and a novel method on the identification of Blog pages was proposed based on the struc-ture of the Blog pages and keywords.The experimental results showe that a high result can be achieved in precision.